Evolutionary dynamics of segmental duplications from human Y-chromosomal euchromatin/heterochromatin transition regions - Kirsch, Stefan; Münch, Claudia; Jiang, Zhaoshi; Cheng, Ze; Chen, Lin; Batz, Christiane; Eichler, Evan E.; Schempp, Werner (Genome Research, 2008)
Human chromosomal regions enriched in segmental duplications are subject to extensive genomic reorganization. Such regions are particularly informative for illuminating the evolutionary history of a given chromosome. We have analyzed 866 kb of Y-chromosomal non-palindromic segmental duplications delineating four euchromatin/heterochromatin transition regions (Yp11.2/Yp11.1, Yq11.1/Yq11.21, Yq11.23/Yq12, and Yq12/PAR2). Several computational methods were applied to decipher the segmental duplication architecture and identify the ancestral origin of the 41 different duplicons. Combining computational and comparative FISH analysis, we reconstruct the evolutionary history of these regions. Our analysis indicates a continuous process of transposition of duplicated sequences onto the evolving higher primate Y chromosome, providing unique insights into the development of species-specific Y-chromosomal and autosomal duplicons. Phylogenetic sequence comparisons show that duplicons of the human Yp11.2/Yp11.1 region were already present in the macaque–human ancestor as multiple paralogs located predominantly in subtelomeric regions. In contrast, duplicons from the Yq11.1/Yq11.21, Yq11.23/Yq12, and Yq12/PAR2 regions show no evidence of duplication in rhesus macaque, but map to the pericentromeric regions in chimpanzee and human. This suggests an evolutionary shift in the direction of duplicative transposition events from subtelomeric in Old World monkeys to pericentromeric in the human/ape lineage. Extensive chromosomal relocation of autosomal-duplicated sequences from euchromatin/heterochromatin transition regions to interstitial regions as demonstrated on the pygmy chimpanzee Y chromosome support a model in which substantial reorganization and amplification of duplicated sequences may contribute to speciation.
10.1101/gr.076711.108